Influence of nitrogen and potassium on production potential of quinoa (Chenopodium quinoa) in India - MOBEENA, SHAIK; THAVAPRAKAASH, N; DJANAGUIRAMAN, M; GEETHANJALI, S; GEETHA, P (The Indian Journal of Agricultural Sciences, 2026)
A field investigation was made during the late Kharif 2022 and Rabi 2022-23 seasons at the Tamil Nadu Agricultural University, Coimbatore, to explore the best nutrient management strategies for enhancing quinoa (Chenopodium quinoa Willd.) production. The experimental field was arranged in a randomized complete block design with nine treatments, each replicated thrice. The treatments included are T1 - 75:0 kg N: K2O/ha, T2 - 100:0 kg N: K2O/ha, T3 - 125:0 kg N: K2O/ha, T4 - 150:0 kg N: K2O/ha, T5 - 75:50 kg N: K2O/ha, T6 - 100:50 kg N: K2O/ha, T7 - 125:50 kg N: K2O/ha, T8 - 150:50 kg N: K2O/ha and, were compared with the Control (T9 - Without N and K2O fertilizers). A 30 kg/ha of phosphorus (P2O5) was commonly applied as basal for all treatments. The results revealed that the application of 150:30:50 kg N: P2O5: K2O/ha (T8) led to superior growth parameters (plant height, leaf area index, drymatter production and number of branches/plant), yield attributes (number of panicle/plant, panicle length, panicle conversion efficiency, number of grains/panicle and test weight), yield (grain and stalk), and economic parameters (gross returns, net returns and benefit: cost ratio) for quinoa, outperforming other treatments except for 150:30:0 kg N: P2O5: K2O/ha (T4) during both seasons. The lowest values across all parameters were recorded for the control (T9). It can be inferred from the investigation that the application of 150:30:50 or 150:30:0 kg N: P2O5: K2O/ha significantly enhanced quinoa’s growth, yield and economic parameters compared to lower nutrient doses in India.